False fame prevented avoiding fluency effects without judgemental correction. [article]. - Topolinski, Sascha
Three studies show a way to prevent fluency effects independently of judgemental correction strategies by identifying and procedurally blocking the sources of fluency variations, which are assumed to be embodied in nature. For verbal stimuli, covert pronunciations are assumed to be the crucial source of fluency gains. As a consequence, blocking such pronunciation simulations through a secondary oral motor task decreased the false-fame effect for repeatedly presented names of actors. (Experiment 1) as well as prevented increases in trust due to repetition for brand names and names of shares in the stock market (Experiment 2) Extending this evidence beyond repeated exposure, we demonstrated that blocking oral motor simulations also prevented fluency effects of word pronunciation on judgements of hazardousness (Experiment 3). Concerning the realm of judgement correction, this procedural blocking of (bising) associative processes is a decontamination method not considered before in the literature, because it is independent of exposure control, mood, motivation, and post hoc correction strategies. The present results also have implications for applied issues, such as advertising and investment decisions.